2022
DOI: 10.1177/03635465221118580
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Fiber Tape Device Versus Transarticular Screws for Ligamentous Lisfranc Injury in a Cadaveric Model

Abstract: Background: The preferred method of fixation and surgical treatment for ligamentous Lisfranc injuries is controversial. Transarticular screws, bridge plating, fusion, and flexible fixation have been described, yet none have demonstrated superiority. Furthermore, screw fixation and plating often require secondary surgery to remove implants, leading surgeons to seek alternative fixation methods. Purpose: To compare transarticular screws and a fiber tape construct under a spectrum of biomechanical loads by evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The first paper compared IB alone with IB with supplemental limbs across the intercuneiform joint in a cadaver model. The second was a cadaver study comparing the InternalBrace (IB) load to failure against screw fixation [ 3 , 11 ]. In these publications, the investigators found that the load to failure was greater if the additional limb was added.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first paper compared IB alone with IB with supplemental limbs across the intercuneiform joint in a cadaver model. The second was a cadaver study comparing the InternalBrace (IB) load to failure against screw fixation [ 3 , 11 ]. In these publications, the investigators found that the load to failure was greater if the additional limb was added.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the true incidence of these fractures may be underestimated [ 2 ]. Signs and symptoms of low-energy Lisfranc injuries may not be as obvious as high-energy injuries but can include severe pain, inability to bear weight, medial plantar bruising, swelling to the affected tarsometatarsal (TMT) joints [ 3 ]. Dorsal subluxation during application of a dorsal force to the forefoot while the other hand palpates the tarsometatarsal joints is suggestive of global instability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a study that shows that the FiberTape device may serve as a viable alternative to screw fixation, while obviating the need for hardware removal. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Lisfranc Injuries Koroneos et al 32 performed a cadaveric biomechanical study comparing suture tape fixation including a dorsal intercuneiform limb (n = 8) and traditional cannulated screws (n = 8) for the fixation of ligamentous Lisfranc injuries. No significant differences were found in gapping at the Lisfranc articulation or the intercuneiform articulation.…”
Section: Traumamentioning
confidence: 99%